EFEKTIVITAS PROGRAM KERJA OSIS DALAM MENINGKATKAN KEMANDIRIAN DAN RASA TANGGUNG JAWAB SISWA DI SMAN 1 NGRAMBE: 10.56997/inisiasi.v4i2.1944 - solikhah, novita maratus; Ulkhaq, Nurul Khusna Diya; Tyas, Zuhriana Widya Rahayu Ning (Inisiasi : Jurnal Manajemen Pendidikan Islam, 2025)
In the school there is an organization called the Intra-School Student Organization (OSIS) which requires a leader who can be an agent of change and can motivate students in their school to be able to realize the vision and mission in an organization. This Intra-School Student Organization (OSIS) is a forum for students to organize in developing themselves in schools that involve students. The purpose of this study was to analyze the effectiveness of the OSIS work program in increasing the sense of independence and responsibility of students at SMAN 1 NGRAMBE.OSIS (student organization in schools) has an important role in developing student character, especially social and leadership skills. Through structured activities, OSIS aims to provide opportunities for students to play an active role, make decisions, and complete tasks independently and responsibly. The method used in this study is a qualitative approach with a survey design directly at school. The data we took were interviews with several OSIS members, one of whom was the OSIS chairman at the school. The findings showed that most students who participated in the OSIS work program experienced a significant increase in independence and responsibility. Activities such as planning school events, managing budgets, and serving on committees are important tools for students to learn time management, teamwork, and overcoming challenges. Thus, the OSIS work program has been proven to be effective in strengthening students' sense of independence and responsibility, thus having a positive impact on their personal and academic development. The study also recommends improving the quality and quantity of OSIS activities so that more students can benefit equally.